Ionophilic Imidazolium-Tagged Cinchona Ligand on LDH-Immobilized Osmium: Recyclable and Recoverable Catalytic System for Asymmetric Dihydroxylation Reaction of Olefins - Kaur, Amanpreet; Singh, Vasundhara (Synlett, 2015)
A catalytic system for the asymmetric dihydroxylation of olefins was developed by using an ionic-tagged biscinchona alkaloid ligand immobilized onto OsO4-exchanged layered double hydroxide (LDH) as a robust recyclable homogenous–heterogeneous catalytic system. The desired products were obtained in high yield and enantioselectivity.
Keywords: asymmetric dihydroxylation; immobilization; catalyst recycling; olefins; (QN)2PHAL-[C5mim]Br; ionic liquid